Template Free Synthesis of Hollow Ball-Like Nano-Fe2O3 and Its Application to the Detection of Dimethyl Methylphosphonate at Room Temperature - Fan, Guokang; Wang, You; Hu, Meng; Luo, Zhiyuan; Zhang, Kaihuan; Li, Guang (Sensors (Basel, Switzerland), 2012)
This paper is focused on the template-free synthesis of nanosized ferric oxide (nano-Fe2O3) and its application in quartz crystal microbalance (QCM) resonators to detect dimethyl methylphosphonate (DMMP), a simulant of Sarin. The X-ray diffraction (XRD) patterns confirm that the synthesized samples are made of Fe2O3 and the scanning electron microscopy (SEM) pictures show that the samples have ball-like shapes. The DMMP sensors with a sensing film of hollow ball-like and solid ball-like Fe2O3 are fabricated and their sensing characteristics are compared. The sensitivity of the hollow ball-like Fe2O3 sensor is more than 500% higher than the one of the solid ball-like Fe2O3 sensor. The hollow ball-like nano-Fe2O3 can be synthesized by a novel low temperature hydrothermal method. The sensors with the hollow ball-like Fe2O3 film perform well in a range of 1 to 6 ppm, with a sensitivity of 29 Hz/ppm at room temperature, while the appropriate recoverability and selectivity are maintained. In addition, the performance of different thicknesses of the sensing film of the hollow ball-like nano-Fe2O3 is investigated and the optimized relative film thickness of the hollow ball-like nano-Fe2O3 is found to be 20 μg/mm2.